Language Ideology and Linguistic Landscape on Business Signboards in Medan - Nurmala, Dewi; Sinar, T. Silvana; Widayati, Dwi; Gustianingsih, Gustianingsih (Proceeding International Conference on Malay Identity, 2024)
The research aimed to analyze the language ideology reflected in language contestation and the language policy used in linguistic landscape in Medan. The research used was qualitative method. The source of data was the photo of business signboards in Medan. The data were the lingual data on the business signboards. After analyzing the data, it was found that the language ideology on business signboards in Medan reflects the nationality, identity and modernity. Besides, the language ideology also shows the power of language that is English to be the dominant language appear in linguistic landscape on business signboards in Medan city. Then, there were 24% of business signboards followed the rule of language policy and 76% of business signboards did not follow the rule of language policy.